HUBUNGAN UKURAN LINGKAR PINGGANG DENGAN SIKLUS MENSTRUASI PADA WANITA USIA SUBUR DI KELURAHAN RENGAS PULAU KECAMATAN MEDAN MARELAN KOTA MEDAN - RATU KISI NABILA SUPRAPTO; IRFAN DARFIKA LUBIS (JURNAL ILMIAH SIMANTEK, 2022)
Waist is a part of the human body located on the horizontal line between the arcus costae and the crista iliaca, the waist is located in the pelvic region. Waist circumference is often used as an alternative marker of abdominal fat mass. The normal menstrual cycle is no less than 21 days and no more than 35 days. Disorders of the menstrual cycle consist of three, namely polymenorrhea, oligomenorrhea, and amenorrhea.This research method is a descriptive analytic method with cross-sectional design approach. The subject of research were 100 woman of childbearing age living in Rengas Pulau, Medan Marelan District, Medan City who met the inclusion and exclusion criteria. .Waist circumference with menstrual cycle has a significant value with a correlation coefficient of 0.259 (p=0.009 Based on the results of this research, it can be concluded that there is no significant correlation between waist circumference and menstrual cycles in the overall sample with weak correlation strength.